Numerical analysis of Savonius hydrokinetic turbine performance in straight and curved channel configurations - Shanegowda T G; Shashikumar C M; Veershetty Gumtapure; Vasudeva Madav (Energy Nexus)
The global shift towards renewable energy has driven research into efficient hydrokinetic energy harvesting, particularly using Savonius turbines for their simplicity and adaptability to low-flow environments. While previous studies have focused primarily on straight channels, the impact of channel bends, commonly found in agricultural canals, rivers, and irrigation channels, remains underexplored. The present 3D transient numerical study addresses this gap by investigating the performance of Savonius hydrokinetic turbines in channels with 30°, 60°, and 90° bends, evaluating their efficiency under varying flow conditions. The research aims to evaluate the impact of these channel bends on key performance parameters such as the tip speed ratio (TSR), torque coefficient (CT) and power coefficient (CP), supported by detailed pressure and velocity contour analyses. The turbine positioned in the 30° bend emerged as the most efficient configuration, achieving a CTmax of 0.29 at 0.7 TSR and CPmax of 0.24 at 1.0 TSR. The 60° and 90° bends exhibited efficiency reductions of 15 % and 30 %, respectively, due to adverse pressure gradients and increased turbulence. Velocity contour plots demonstrated reduced wake regions and optimized flow reattachment for the 30° bend, while pressure contour analysis indicated lower drag forces on the advancing blades. This study highlights the potential of using Savonius turbines in agricultural channels, recommending the 30° bend as the optimal channel configuration to maximize turbine efficiency, providing a sustainable solution for energy generation in rural and low-flow environments.